Pertumbuhan cabai (Capsicum annuum L.) dengan pemberian Gigaspora margarita dan bokashi jerami padi pada tanah gambut - Mukarlina, Agus Merdekawati, Riza Linda, (Universitas Tanjungpura, 2014)
Peat soil has nutrient availability which is relatively low and soil acidity which is high and therefore contributes to the growth of hybrid pepper (Capsicum annuum). One of the efforts to improve the growth of hybrid pepper is by using Vesicles Arbuscular Mycorrhizal fungus (VAM) Gigaspora margarita and rice straw bokashi as organic fertilizer. This study aims to determine the growth of hybrid pepper plants on peat soil which is inoculated with VAM fungi and rice straw bokashi. This research had been done from August to November 2013.Â The findings of MVA inoculated fungi did not significantly affect on the plant height and number of leaves but significantly affect on wet weight, dry weight and the percentage of root infection. The treatment of rice straw bokashi did not significantly affect the plant height, the numbers of leaves and the wet weight but significanty affect on the dry weight and percentage of root infection. The interaction between VAM and rice straw bokashi had no significant effects on all the parameters observed. The concentrations of VAM fungal inoculation VAM and the treatment of rice straw bokashi showed that the highest influence on each parameter is 15 g and 600 g respectively.